2013
DOI: 10.1002/hbm.22315
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor‐independent prefrontal activity during response inhibition

Abstract: A network of brain regions involving the ventral inferior frontal gyrus/anterior insula (vIFG/AI), presupplementary motor area (pre-SMA) and basal ganglia has been implicated in stopping impulsive, unwanted responses. However, whether this network plays an equal role in response inhibition under different sensorimotor contexts has not been tested systematically. Here, we conducted an fMRI experiment using the stop signal task, a sensorimotor task requiring occasional withholding of the planned response upon th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 104 publications
(150 reference statements)
4
23
2
Order By: Relevance
“…Relevant to both proactive and reactive inhibitory control, the anodal tDCS on the right IFG has been shown to change its excitability and its functional connectivity with the pre-SMA (Cai, Cannistraci, Gore, & Leung, 2014;Aron, 2011;Aron & Poldrack, 2006), which is another important area implicated in both inhibitory control processes (Aron, 2011;Wardak, 2011;Chen, Scangos, & Stuphorn, 2010). For example, a diffusion tensor imaging study showed that the right IFG and pre-SMA were structurally connected (Aron et al, 2007) and the strength of this anatomical connectivity predicted performance on an inhibitory task (Buch, Mars, Boorman, & Rushworth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to both proactive and reactive inhibitory control, the anodal tDCS on the right IFG has been shown to change its excitability and its functional connectivity with the pre-SMA (Cai, Cannistraci, Gore, & Leung, 2014;Aron, 2011;Aron & Poldrack, 2006), which is another important area implicated in both inhibitory control processes (Aron, 2011;Wardak, 2011;Chen, Scangos, & Stuphorn, 2010). For example, a diffusion tensor imaging study showed that the right IFG and pre-SMA were structurally connected (Aron et al, 2007) and the strength of this anatomical connectivity predicted performance on an inhibitory task (Buch, Mars, Boorman, & Rushworth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in inhibitory control are often assessed by calculating a stop-signal reaction time (SSRT), which provides an index of how long it takes an individual to inhibit the response, and thus the strength of their inhibitory ability. Differences in SSRT across individuals relate to activation of a number of neural systems involved in the “stopping network”, including right inferior frontal gyrus, posterior parietal cortex, and pre-supplementary motor areas (Aron, 2007; Cai et al, 2013; Congdon et al, 2010). Individuals with shorter SSRTs, reflective of stronger/faster inhibition, typically show greater activation of these neural systems on inhibition trials.…”
Section: Introductionmentioning
confidence: 99%
“…They found that response inhibition correlated with activity in right inferior frontal cortex while error performance correlated with mesial frontopolar and bilateral inferior frontal cortex. Furthermore, Cai et al [74] subjects. They found that activation in inferior frontal gyrus, middle frontal gyrus and basal ganglia was modality independent.…”
Section: Anatomy Of Processing Speed Working Memory and Inhibitionmentioning
confidence: 99%